2014
DOI: 10.1080/15299732.2014.880772
|View full text |Cite
|
Sign up to set email alerts
|

Is the Dissociative Adult Suggestible? A Test of the Trauma and Fantasy Models of Dissociation

Abstract: Psychologists have long assumed a connection between traumatic experience and psychological dissociation. This hypothesis is referred to as the trauma model of dissociation. In the past decade, a series of papers have been published that question this traditional causal link, proposing an alternative fantasy model of dissociation. In the present research, the relationship among dissociation, suggestibility, and fantasy proneness was examined. Suggestibility was measured through the Gudjonsson Scale of Interrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Merckelbach, Wiers, et al (2001) administered the CEQ and ICMI to a group of 52 students and obtained a correlation of 0.77 between both measures. Kluemper and Dalenberg (2014) included both the CEQ and ICMI in their study on suggestibility in adults ( N = 92) and found a correlation of 0.87. Plante et al (2017) gave the CEQ and a subset of ICMI items that probe anomalous beliefs to their participants ( N = 124) and reported a correlation of 0.71 between both measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Merckelbach, Wiers, et al (2001) administered the CEQ and ICMI to a group of 52 students and obtained a correlation of 0.77 between both measures. Kluemper and Dalenberg (2014) included both the CEQ and ICMI in their study on suggestibility in adults ( N = 92) and found a correlation of 0.87. Plante et al (2017) gave the CEQ and a subset of ICMI items that probe anomalous beliefs to their participants ( N = 124) and reported a correlation of 0.71 between both measures.…”
Section: Resultsmentioning
confidence: 99%
“…Following the study by Wilson and Barber (1983), many researchers ascribed the genesis of fantasy proneness to adverse childhood experiences and trauma-related psychopathology, particularly dissociative symptoms, and argued that fantasy proneness is fueled by a need to escape adverse childhood experiences and functions as an automatized habitual defensive FANTASY PRONENESS: A META-ANALYSIS reaction (e.g., Bottoms et al, 2012Bottoms et al, , 2016Lawrence et al, 1995). Kluemper and Dalenberg (2014), for example, contended that fantasy proneness and dissociative symptomatology overlap because both originate from a traumatic history and both involve absorption (i.e., a state of strong attentional focus), which could be construed as a mental flight from aversive memories (see also Allen & Coyne, 1995). However, Lynn and Rhue (1988; see also Hilgard, 1974) reported that apart from a history of trauma and isolation, a nonmalign pathway to fantasy proneness is acculturation in a nurturing environment that stimulates creativity and adaptive, enjoyable fantasy activities.…”
Section: Traumamentioning
confidence: 99%
“…Conversely, finding that sleep would remain robust whereas distress would not, would support the SM over the DM, suggesting that sleep may indeed be the pertinent factor explaining the effect of distress on dissociation. Finally, it should be noted that the present study does not examine the socio‐cognitive or “fantasy” model explaining dissociation (Giesbrecht et al, 2008; Spanos, 1994), which is considered as a rival theory to the trauma model (Dalenberg et al, 2014; Kluemper & Dalenberg, 2014; Lynn et al, 2014), as it concerns the veracity of trauma reports by dissociative individuals which is outside of the scope of the present investigation. Acknowledging this debate is important as critical views towards the trauma theory have crucial implications for patients suffering from dissociative disorders (Leonard et al, 2005; Loewenstein, 2018) or those recalling past trauma (Dalenberg et al, 2020), but our sample characteristics and data collection design are not suitable to contribute to the trauma versus fantasy issue.…”
Section: The Path To Dissociative Experiences: a Direct Comparison Of Different Etiological Modelsmentioning
confidence: 92%
“…The measure has strong test–retest and internal reliability of r > .82 (Dalenberg, 1983), and was shown to differentiate a court-ordered sample of child abuse victims from a normative sample. The VHQ has been shown to relate to posttraumatic stress symptoms (Dalenberg, 1983), attachment status (Coe, Dalenberg, Aransky, & Reto, 1995), and dissociation (Kluemper & Dalenberg, 2014). The VHQ had not been published at the time of this study, and was one of the scales including in the norming study to develop validity data on its relationship to other measures.…”
Section: Methodsmentioning
confidence: 99%